Injuries among children and adolescents in a rapidly growing urban African metropolis: a cross-sectional survey of 1,968 households in Dar es Salaam, Tanzania - Pérez Méndez, Mónica Alejandra; Kigwangalla, Hamisi A.; Bärnighausen, Till; Wilson, Michael (PeerJ, 2020)
Objectives To assess the patterns and incidence of child and adolescent injury and explore associations with household deprivation and child characteristics in a low-income urban setting. Study Design Cross-sectional household survey in Dar es Salaam, Tanzania. Methods Data collection took place during July 2009. Injuries requiring medical attention were recorded with a one month period of recall. A total of 1,968 households representing 3,927 children and adolescents were visited by health workers. Gender-, age-, and type-specific injury incidence was compiled. Odds ratios were calculated to measure associations with child injury, perceived deprivation, household characteristics and child characteristics. Results One household in five reported injuries. The estimated incidence was 3.2 per 10,000 child-years. The most common identifiable injuries were falls (41%), cuts (22%) and burns (16%). Male and younger children aged 1-4 years were at higher risk (respectively OR = 1.36; p = 0.004; OR = 1.47; p ≤ 0.001). Conclusions In Dar e Salaam injuries are common. Future investigations should take into account both subjective and objective measurements of relative household deprivation and a clear criteria for the assessment of injury severity in community-based survey contexts.
Gesehen am 04.11.2020